Psychological Problems Reflected in SpencerMovie (2021): A Psychoanalytic Perspective - Murti, Bharatu Nata; Nugroho, Abdillah (Universitas Negeri Semarang, 2024)
Psychoanalysis is a theory that assumes that a person's personality develops when a conflict and psychological aspect occurs. In this article, the researcher examines the mental disorder or depression experienced by Princess Diana in the film. Psychoanalytic theory and hermeneutic and qualitative methodologies are used by researchers in the research of this article. The data used by the researcher included text and images as a form of psychological disclosure experienced by Princess Diana. The overwhelming stress in this film culminates in the depression experienced by Princess Diana. This research provides insight into Princess Diana's internal life struggles in dealing with her mental health, as well as describing the impact of marriage and public life. This article discusses the importance of managing mental health awareness represented in the value of psychoanalytic theory. The film